The infinity gauntlet aftermath ebook - Marz, Ron (Marvel Worldwide, Inc., 2014)
Collects Silver Surfer (1987) #60-66, Dr. Strange : Sorcerer Supreme #36, Warlock & the Infinity Watch #1-6, material from Silver Surfer Annual 5. After defeating Thanos, Adam Warlock won the Infinity Gauntlet - and now has absolute power! Can the most powerful being in the universe be convinced to give up the Gauntlet? And who can be trusted with even a portion of its awesome abilities? Meanwhile, the Silver Surfer races to destroy Thanos' shrine to Death - but first he must contend with onetime Infinity Gem owner the Collector, and face his darkest fears!